Interview for KPFA with Mark Wilson - Russ Jennings::::::::: (1988)
[00:00:01] Wilson introduces Sarah Boutelle and provides her academic credentials [00:00:57] Wilson asks how Boutelle went about gathering information for her book [00:01:40] Boutelle states that she wanted to create a full catalog of all of Morgan's buildings [00:02:38] Boutelle says her biggest sources were the people who came to her her lectures in order to tell of Morgan's buildings or clients that Boutelle was unaware of [00:03:08] Boutelle states that the colleges did not have any courses or information on Morgan [00:03:27] Wilson asks how Boutelle gathered plans and office records since Morgan had most of her records destroyed [00:05:23] Boutelle talks about her 180 degree switch on her opinion of William Randolph Hearst through reading his correspondence with Julia Morgan [00:08:16] Boutelle discusses how she found the photographer for her book, Richard Barnes, after seeing his photographs on the cover of California Alumni magazine [00:09:54] Boutelle discusses the attention given to Bernard Maybach's career and mostly denies sexism as the reason why Morgan was often overlooked as an architect [00:12:11] Boutelle talks about Morgan's output as an architect relative to her contemporaries Bernard Maybach and Frank Lloyd Wright [00:14:48] Boutelle talks about Morgan's professional network that was started with her sorority sisters and Phoebe Hearst [00:16:53] Boutelle discusses Morgan's philosophy of design in residential homes that combined California and European styles as a result of her Beau-Arts training for "the plan" [00:18:46] Boutelle talks about Morgan's credo to be an architect without emphasis on her womanhood, but encouraged her female employees to their architectural licenses to be listed as assistant architects [00:21:00] Boutelle discusses other female architects in the Bay Area at the time and their influences from Oakland and buildings around them [00:22:09] Boutelle discusses the 20th century "social movement" of women's clubs and the funding, building, design of the Berkeley City Club [00:24:21] Boutelle states that one of Morgan's most important contributions was her work providing housing for single women as it tackled a social problem and represented a new kind of urban housing [00:25:32] Wilson thanks Buotelle for her contributions and ends the interview